Monocyte activation in systemic Covid-19 infection: Assay and rationale (2020)
Mononuclear phagocytes are a widely distributed family of cells contributing to innate and adaptive immunity. Circulating monocytes and tissue macrophages participate in all stages of SARS COVID-19. They contribute to comorbidities predisposing to clinical infection, virus resistance and dissemination, and to host factors that determine disease severity, recovery and sequelae. Assays are available to detect viral infection and antibody responses, but no adequate tests have been developed to measure the activation level of monocytes and tissue macrophages, and the risk of progression to a fatal hyperinflammatory syndrome. Blood monocytes provide a window on the systemic immune response, from production to tissue recruitment, reflecting the impact of infection on the host. Ready availability of blood makes it possible to monitor severity and the risk of potentially lethal complications, by developing tests to assess the status of monocyte activation and its potential for further inflammatory dysregulation after recruitment to tissues and during recovery.